Goldcore–polyanilineshell composite nanowires as a substrate for surface enhanced Raman scattering and catalyst for dye reduction. (19th November 2014) - Dutt, Sunil; Siril, Prem Felix; Sharma, Vipul; Periasamy, Selvakannan
Abstract : The unique morphology of the nanocomposite is due to the confinement, typical diffusion path and the interaction between PANI and Au-nanoparticles. Abstract : Composite nanowires with a gold core (Aucore ) and polyaniline shell (PANIshell ) were prepared using swollen liquid crystals (SLCs) as a soft, structure directing template. The composite nanowires were prepared by simply pouring the SLC containing AuCl3 over the SLC containing aniline. SLCs were formed by a quaternary mixture containing brine, sodium dodecyl sulphate (SDS) as the surfactant, 1-pentanol as the co-surfactant and cyclohexane as oil. A portion of cyclohexane was replaced by aniline to make SLCs containing aniline in the oil phase. Similarly, brine was replaced with a solution of gold chloride to make the mesophase containing Au 3+ ions. Simultaneous chemical oxidation of aniline and reduction of Au 3+ ions takes place upon mixing the above mentioned mesophases, leading to the formation of the nanocomposite. Small spherical nanoparticles or short nanorods that are initially formed join together to form nanowires within the PANI shell due to the confinement, typical diffusion path and also due to the strong interaction between Au and PANI. The prepared composite nanowires exhibited good surface enhanced Raman scattering (SERS) for an organic dye. The composite also showed excellent catalytic behavior for the chemical reduction of organic dyes.